THE SOCIAL CONFLICT EXPERIENCED BY THE MAINCHARACTER IN NOVEL CHARLES’ DICKENS’ NOVEL“GREAT EXPECTATIONS” - Wati, Ambar; Nur, Sahril (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study discusses social conflict in the novel Great Expectations. Every paragraph has a conflict in it. Readers should look more deeply at each meaning in the novel to make it easier tounderstand. The theory used in analyzing this novel is the theory of social conflict by Lewis A Coser(2002), which categorizes it into three elements, namely Conflict concerning social statuses, Conflict of interest, and Conflict of role. The problem of this research is to find out the social conflict (conflict concerning social statuses, conflict of interest and conflict of role) in the noveland also to find out how it affects the reader. The are 13 cases identifying of Social Conflict: 7 data identifying of conflict concerning social statues, 3 data identifying conflict of interest, and3 data identifying conflict of role. The method used in this research is descriptive qualitative because the data analyzed is in the form of sentences. The social conflict in the novel is the storyof the main character. The mode in the novel is personal distance, written and spoken. The influence of social conflict on readers is closely related because it is often found in everyday lifeto help people conclude various kinds of conflicts that are often encountered.